(untitled) (Nexo Revista Científica, 2022)
In this paper, to determine the main knowledge streams of technological learning in joint R&D (JRD) projects in petroleum industry, the co- word analysis method is used. The knowledge map is drawn by reviewing 388 papers published in the study area from 2000 to 2021 in Scopus and Sage databases using VOSviewer1.6.16 software. Accordingly, by reviewing the existing knowledge, the two main concepts of knowledge management and technological innovation are identified. Then, using text mining method and drawing a concept knowledge map, 8 clusters are extracted and their relationships are analyzed using Netdraw software. Finally, the study period from 2000 to 2021 is divided into three main categories: organizational - communication characteristics, economic goals and concepts of innovation, and shown the most focus in recent years is in the field of innovation concepts.